MODEL STRATEGIS BERBASIS INTEGRASI METODE UNTUK MENGATASI KETIDAKPERCAYAAN DIRI DALAM BERBAHASA INGGRIS - Azmi, Nurul; Rambe, Khairul Fadli; Afifah, Syifa Tsany (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
In today's era of globalization, English language proficiency has become a fundamental competency. Unfortunately, many students and university students still struggle to communicate fluently in English. This study aims to identify and analyze psychological factors, particularly lack of confidence, which are the main obstacles to students' and university students' English speaking skills. It also offers relevant teaching strategies to improve students' English speaking skills and confidence. The method used in this study is library research. The nature of this research is descriptive analysis, which involves the systematic interpretation of the data obtained and then providing explanations so that it can be understood by readers. The results of the study show that both the Grammar Translation Method (GTM) and the Direct Method have the potential to be effective in teaching English. The Grammar Translation Method (GTM) excels in grammar comprehension, sentence structure, reading, and translation, supporting the mastery of English as a second language. Meanwhile, the Direct Method encourages spontaneous oral communication and boosts confidence through the direct use of the target language without translation into the mother tongue. Overall confidence is crucial in encouraging students to speak and overcome their fears.